How Do Music Activities Affect Health and Well-Being? A Scoping Review of Studies Examining Psychosocial Mechanisms - Dingle, Genevieve A.; Sharman, Leah S.; Bauer, Zoe; Beckman, Emma; Broughton, Mary; Bunzli, Emma; Davidson, Robert; Draper, Grace; Fairley, Sheranne; Farrell, Callyn; Flynn, Libby Maree; Gomersall, Sjaan; et al. (Frontiers in Psychology, 2021)
Background: This scoping review analysed research about how music activities may affect participants’ health and wellbeing. Primary outcomes were measures of health (including symptoms and health behaviours) and wellbeing. Secondary measures included a range of psychosocial processes such as arousal, mood, social connection, physical activation or relaxation, cognitive functions, and identity. Diverse music activities were considered: receptive and intentional music listening; sharing music; instrument playing; group singing; lyrics and rapping; movement and dance; and songwriting, composition, and improvisation. Methods: Nine databases were searched with terms related to the eight music activities and the psychosocial variables of interest. Sixty-three papers met selection criteria, representing 6,975 participants of all ages, nationalities, and contexts. Results: Receptive and intentional music listening were found to reduce pain through changes in physiological arousal in some studies but not others. Shared music listening (e.g., concerts or radio programs) enhanced social connections and mood in older adults and in hospital patients. Music listening and carer singing decreased agitation and improved posture, movement, and wellbeing of people with dementia. Group singing supported cognitive health and wellbeing of older adults and those with mental health problems, lung disease, stroke, and dementia through its effects on cognitive functions, mood, and social connections. Playing a musical instrument was associated with improved cognitive health and wellbeing in school students, older adults, and people with mild brain injuries via effects on motor, cognitive and social processes. Dance and movement with music programs were associated with improved health and wellbeing in people with dementia, women with postnatal depression, and sedentary women with obesity through various cognitive, physical, and social processes. Rapping, songwriting, and composition helped the wellbeing of marginalized people through effects on social and cultural inclusion and connection, self-esteem and empowerment. Discussion: Music activities offer a rich and underutilized resource for health and wellbeing to participants of diverse ages, backgrounds, and settings. The review provides preliminary evidence that particular music activities may be recommended for specific psychosocial purposes and for specific health conditions.